Gallbladder preserving cholelithotomy in children with hereditary spherocytosis complicated by gallstones: a single-center retrospective study - Tang, Ran; Zhou, Cheng-xiao; Yang, Yong; Bian, Jian; Meng, Li-xiang; Wei, De-cheng; Qi, Shi-qin (Frontiers in Pediatrics, 2024)
Background: Gallstones are among the most common complications of hereditary spherocytosis (HS). In previous treatments, gallbladder-preserving cholelithotomy (GPC) has remained a subject of significant debate due primarily to potential risks of stone recurrence. However, past studies have often overlooked the impact of specific disease conditions on GPC. In this study, we reviewed the clinical data of GPC in HS pediatric patients with concurrent gallstones over a period of seven years in a single center.From December 2016 to April 2024, 32 pediatric patients with HS who underwent splenectomy and GPC surgery based on our inclusion criteria. Clinical pathological, and follow-up data of these patients were collected.Results: In terms of short-term complications, there were there were no cases of postoperative bleeding, bile duct injury. 3 cases (9.3%) experienced varying degrees of bile peritonitis. During long-term follow-up, only 2 cases (6.2%) showed recurrence of gallstones. One case of bile leakage occurred. Conclusion:GPC demonstrates significant efficacy for pediatric patients with hereditary spherocytosis (HS) complicated by gallstones, showing a a low recurrence rate and high safety profile.